Two new species of Echinosepala (Orchidaceae: Pleurothallidinae) - Pupulin, Franco; Karremans, Adam P.; Belfort Oconitrillo, Noelia (Lankesteriana: International Journal on Orchidology, 2017)
We describe and illustrate two new species of Echinosepala from Costa Rica, they are placed within a phylogenetic framework of the genus, and compared to their closest relatives. A short resume of the genus’ history is given, reviewing the main characters that have been used to group its species at various taxonomic ranks. Echinosepala expolita is compared with E. pan, from which it mainly differs by the glabrous, inflated sheaths that cover the ramicaul, the distinctly broader ligulate-lanceolate leaves, the lanate-hirsute ovary, the much larger flower, and the tomentose abaxial indumentum of the sepals. Echinosepala longipedunculata is similar to E. aspasicensis, but can be recognized by the unusually long peduncle, the greenish yellow flower, the verrucose-tuberculate adaxial surface of the sepals, and the shorter, truncate, orange lip. A key to the Costa Rican species of Echinosepala is provided. A new combination in Echinosepala is proposed for Acianthera biseta from Peru.